2016
DOI: 10.3758/s13421-016-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

When children forget to remember: Effects of reduced working memory availability on prospective memory performance

Abstract: The preparatory attentional and memory processes theory (PAM) of prospective memory (PM) proposes that prospective remembering is influenced by the variation in the availability of WM resources. Consequently, PM should be impaired when WM resources are reduced either by direct WM manipulation or by individual differences associated with restricted WM performance. Our study tested this prediction in school-age children by examining the independent and interactive effects of three factors known to deplete availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Hence, records in other languages, commentaries, narrative/qualitative reviews, editorials, book chapters, and abstracts were not considered for further analysis. The following exclusion criteria were also applied: (a) studies that manipulated the cognitive load of the PM cue (e.g., Ballhausen et al, 2017 ; Cohen, 2013 ), as these conditions have been shown to affect OT performance ( Meier & Zimmermann, 2015 ), (b) studies that included delay-execute conditions or activity-based PM tasks (i.e., the PM response had to be performed after a particular task has finished; Brewer et al, 2011 ), as PM cues did not appear during the OT, (c) studies that included clinical samples, as PM might be particularly affected in this context (e.g., Albinski et al, 2012 ), (d) studies that involved drug interventions and/or ingestion of substances (e.g., Rusted, & Trawley, 2006 ), or that manipulated other factors including sleep (e.g., Barner et al, 2016 ), or that used neuromodulation techniques such as transcranial magnetic stimulation (e.g., Basso et al, 2010 ), (e) experiments that included children, adolescents, and older adults (e.g., Cheie et al, 2017 ; Zollig et al, 2007 ) given that previous research had demonstrated that PM follows an inverted U-shape developmental trajectory ( Zuber & Kliegel, 2019 ; Zimmermann & Meier, 2006 ). So, by including only young and middle-age adults, age effects were somewhat restricted to this developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, records in other languages, commentaries, narrative/qualitative reviews, editorials, book chapters, and abstracts were not considered for further analysis. The following exclusion criteria were also applied: (a) studies that manipulated the cognitive load of the PM cue (e.g., Ballhausen et al, 2017 ; Cohen, 2013 ), as these conditions have been shown to affect OT performance ( Meier & Zimmermann, 2015 ), (b) studies that included delay-execute conditions or activity-based PM tasks (i.e., the PM response had to be performed after a particular task has finished; Brewer et al, 2011 ), as PM cues did not appear during the OT, (c) studies that included clinical samples, as PM might be particularly affected in this context (e.g., Albinski et al, 2012 ), (d) studies that involved drug interventions and/or ingestion of substances (e.g., Rusted, & Trawley, 2006 ), or that manipulated other factors including sleep (e.g., Barner et al, 2016 ), or that used neuromodulation techniques such as transcranial magnetic stimulation (e.g., Basso et al, 2010 ), (e) experiments that included children, adolescents, and older adults (e.g., Cheie et al, 2017 ; Zollig et al, 2007 ) given that previous research had demonstrated that PM follows an inverted U-shape developmental trajectory ( Zuber & Kliegel, 2019 ; Zimmermann & Meier, 2006 ). So, by including only young and middle-age adults, age effects were somewhat restricted to this developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…WM is required in PM tasks to actively sustain the intention while the individual is involved in the ongoing task; accordingly, WM has been found to be a predictor of PM performance in children and adults [23,32,33]. Thus, the manipulation of WM load in experimental paradigms should influence PM performance, as suggested by a number of studies [34,35]. A recent study conducted in a group of healthy adults found that in the time-based condition, but not in the event-based condition, prospective remembering was affected by the reduction of WM resources [36].…”
Section: Cognitive Factors Underlying Prospective Memory Performancementioning
confidence: 99%
“…Participants with higher span scores showed greater costs than participants with lower span scores in the OT, indicating that high-span participants were more prone to engage in preparatory attentional processes. Similarly, Cheie et al (2017) showed that increasing processing demands on the OT or imposing an additional WM span on children compromised their performance.…”
Section: Introductionmentioning
confidence: 99%